Empowering the Creative Economy through Weaving Artisanship for Community Welfare in Central Lombok: An Islamic Economic Perspective - Bathin Bathin; Mashur Mashur (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
This study explores the empowerment of the creative economy through weaving artisanship as a means of improving community welfare in Central Lombok, Indonesia, from the perspective of Islamic economics. The research is motivated by the increasing recognition of creative industries as strategic drivers of inclusive and sustainable development, particularly in rural areas where cultural heritage and local craftsmanship remain strong. Using a qualitative descriptive method, data were collected through interviews, observations, and documentation involving local weavers, community leaders, and supporting institutions in Rembitan Village, Pujut District. The findings reveal that weaving activities have significantly contributed to the enhancement of family welfare, as reflected in increased household income, improved access to education, and strengthened community solidarity. The artisans’ economic empowerment was achieved through the provision of facilities, training, and skill-sharing mechanisms supported by local and governmental initiatives. However, several challenges persist, including limited access to capital, market expansion, and digital literacy. From an Islamic economic perspective, weaving enterprises embody ethical principles such as halal production, honesty (ṣidq), hard work (ijtihād), and the prohibition of exploitative profit (gharar and riba’). The study concludes that empowering traditional artisans through creative economic activities grounded in Islamic values can enhance both material and spiritual well-being. It recommends collaborative policies involving local government, religious institutions, and private sectors to strengthen creative entrepreneurship, promote digital marketing, and institutionalize sharia-compliant financing schemes for artisan communities.